Food bank operational characteristics and rates of food bank use across Britain - Rachel Loopstra; Hannah Lambie-Mumford; Jasmine Fledderjohann (BMC, 2019)
Abstract Background Food banks are a common community-based response to household food insecurity in high-income countries. While the profile of their users and nature of the quality of food they provide have been researched, few studies have examined their operational characteristics to explore the accessibility of their services for people at risk of food insecurity. This study describes the nature of operations in a food bank network operating in Britain and explores how operations are associated with volume of use. Methods Data from The Trussell Trust Foodbank's network of 1145 distribution centres in 2015/16 on hours of operation, locations, and usage were combined with national statistics on Working Tax Credit claimants, disability and unemployment. Descriptive statistics focused on how often and when food banks were open within local authorities. The relationships between operational characteristics and volume of use were examined using regression analyses. Interaction terms tested how relationships between indicators of need with food bank usage changed with operational characteristics. Results Weekday operating hours were primarily between the hours of 10 a.m. and 2 p.m., but at any given hour no more than 20% of distribution centres were open, with fewer than 3% open after 4 pm. Where food banks had fewer distribution centres and operating hours, the volume of food bank usage was lower. In-work poverty, disability, and unemployment rates were all associated with higher volume of usage; however, the relationship between disability and food bank use was modified by the density of food banks and number of operating hours. Where food banks were less accessible, the relationship between disability and food bank use was diminished. Conclusions These findings suggest operational characteristics are an important part of access to food banks and raise questions about the ability of food banks to meet the needs of people at risk of food insecurity in Britain.